Minimum latency data aggregation scheduling in MR-MC wireless sensor networks - Jin-bao LI; Meng WANG; Long-jiang GUO (Tongxin xuebao)
The problem of minimum latency data aggregation scheduling in single-radio single-channel wireless sensor networks is a NPC problem and many solutions have been proposed.In multi-radio multi-channel networks,the latency may be lower as a node may receive transmission data from other different nodes simultaneously.It formulates the minimum latency data aggregation scheduling into an optimization problem with joint consider of tree structure,time slot assignment,channel assignment and radio assignment.The problem is divided into constructing data aggregation tree and designing a node schedule subproblems.For each subproblem,heuristic algorithm has been proposed.The simulation results show that the proposed algorithm achieve good performance.